Influence of selected non-operative treatment methods of urinary stress incontinence on patients’ life quality - Wlaźlak, Edyta; Surkont, Grzegorz; Stetkiewicz, Tomasz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2005)
Today, there is not known the exact influence of urinary stress incontinence and different modalities of treatment on women’s quality of life. Intensification of symptoms of urinary incontinence and its influence on patient’s life is usually evaluated by physician himself. But this kind of analysis is probably not sufficient. Most of urogenital symptoms can be evaluated by special questionnaires filled by patients themselves, recommended by I and II Consultation on Incontinence (Monako 1998, Paris 2002). The aim of this study was to evaluate the influence of non-operative ways of treatment of stress urinary incontinence (Kegel’s exercises, vaginal estrogens) on patient’s quality of life. Results. 30.4% (14/46) of women were satisfied with the results of treatment. There was correlation between satisfaction and symptoms evaluated by doctors examination (r=0.557; p<0,01). Non-operative treatment had rather strong positive influence on quality of life – 37% (17/46) of women showed strong positive influence on quality of life, evaluated with IIQ-7 questionnaire. Great progress of quality of life correlated with shortage of symptoms of stress urinary incontinence (r=0.447; p<0.01). Conclusions. Treatment with Kegel’s exercises and vaginal estrogens is effective on progress of quality of life of patients. Its influence has weak correlation with efficiency of non-operative modalities of treatment.